An insight into Mg alloying effects on Cu thin films: microstructural evolution and mechanical behavior. (15th November 2020) - Li, G.Y.; Cao, L.F.; Zhang, J.Y.; Li, X.G.; Wang, Y.Q.; Wu, K.; Liu, G.; Sun, J.
Abstract: How to design ultra-strong, light-weight Cu alloys is a long-term pursuit in materials community, which is technically superior and cost-effective for their promising energy-saving applications. In this work, we prepared Cu-Mg alloyed thin films to study light element Mg alloying effects on the microstructure, hardness and strain rate sensitivity (SRS) of nanocrystalline Cu thin films. In the studied Mg concentration-range spanning from 0 at.% to 16.8 at.%, both the grain size and the twin spacing decrease monotonously with increasing Mg composition while Cu-2.8 at.% Mg sample has the highest twin fraction of ∼75%. A combined strengthening model was employed to quantify the Mg concentration-dependent hardness of nanotwinned (NT) Cu-Mg thin films, in which the grain/twin boundary facilitates strengthening while the solute Mg atoms induce softening. Both the constant rate of loading tests and the nanoindentation creep tests uncover that compared with pure Cu samples, the NT Cu-Mg thin films manifest much lower SRS, particularly in the creep tests, owing to the activation of dynamic strain aging effects.